Research Trends in Project-Based Science Modules to Enhance Scientific Literacy, Environmental Literacy, and Entrepreneurial Motivation - X. Zardht Alex Hidayat; A. Wahab Jufri; I Putu Artayasa (Balai Publikasi Indonesia, 2025)
This research aims to identify and analyze research related to module development in increasing scientific literacy, entrepreneurial motivation and environmental literacy. This research uses descriptive and analytical methods. Data was obtained from documents indexed by Google Scholar in the period 2015-2024, using the Publish or Perish and Dimension.ai tools. Research procedures refer to PRISMA guidelines. The data studied includes types of publications, publication sources, as well as widely cited research titles regarding the development of science modules in increasing scientific literacy, entrepreneurial motivation, and environmental literacy. Data analysis was carried out using bibliometric methods with the help of VOS Viewer software. The results of research regarding the development of project-based science modules to increase scientific literacy, entrepreneurial motivation and environmental literacy indexed in Google Scholar from 2015 to 2024 were mostly carried out separately and few were carried out by combining the three additional variables. The graphic results show an increase, but when seen in quantity the amount is still small. Many documents in the form of articles, proceedings, book chapters, preprints, and edited books discuss research on project-based learning models to improve problem solving skills in science learning. Key words that are often used in this research include Environmental literacy, Environmental knowledge, Students motivation, Project work, and Environmental education